Reducing Sequence Risk Using Trend Following and the CAPE Ratio. Issue 4 (1st October 2017) - Clare, Andrew; Seaton, James; Smith, Peter N.; Thomas, Stephen
Abstract : The risk of experiencing bad investment outcomes at the wrong time, or sequence risk, is a poorly understood but crucial aspect of the risk investors face—particularly those in the decumulation phase of their savings journey, typically over the period of retirement financed by a defined contribution pension scheme. Using US equity return data for 1872–2014, we show how this risk can be significantly reduced by applying trend-following investment strategies. We also show that knowing a valuation ratio, such as the cyclically adjusted price-to-earnings (CAPE) ratio, at the beginning of a decumulation period is useful for enhancing sustainable investment income. Abstract : Disclosure: The authors report no conflicts of interest. Editor's Note Submitted 8 September 2016 Accepted 28 April 2017 by Stephen J. Brown